Teachers’ Roles on Constructing English Medium Instruction Policy in Community Schools - Ghimire, Nani Babu; Pandeya, Yam Prasad; Gurung, Bhanu Bhakta (Journal of Tikapur Multiple Campus, 2025)
Community schools have adopted English Medium Instruction (EMI) policy in response to the increasing influence of the English language in the world including Nepal. This study investigates the roles of teachers in constructing EMI policy in community schools. Employing a qualitative ethnographic research design, the study examines the opinions and experiences of three Grades (VI-VIII) teachers from three EMI community schools in the Sindhuli district. We collected data through in-depth interviews, participant observations, and field notes, gaining rich insights into the contextual realities of the schools. We transcribed audio-recorded interviews, translated them into English, coded, and categorized the data to derive key themes, offering a nuanced understanding of the teachers’ experiences and practices. The study divulges that the effective execution of EMI policy in Nepal’s community schools is hindered by the limited involvement of teachers in policy construction. Moreover, the findings highlight that SMCs and head teachers predominantly adopt a top-down approach to EMI policy construction, treating teachers primarily as implementers rather than policy creators. To enhance the effectiveness of EMI policy, the study offers a more inclusive bottom-up approach needs to be followed by SMCs and head teachers with active engagement of teachers in the development, planning, and review of EMI policy.